Parental leave benefit and differential fertility responses: Evidence from a German reform - Kamila Cygan-Rehm (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2013)
This paper examines the causal effects of a major change in the German parental leave benefit scheme on fertility. I use the unanticipated reform in 2007 to assess how a move from a means-tested to an earnings-related benefit affects higher-order births. By using the German Mikrozensus 2010, I find that the reform significantly affected the timing of higher-order births in the first three years. Overall, mothers initially reduce childbearing, thereby extending their birth spacing, but eventually fully compensate for the earlier losses. The negative effects are largely driven by lowest-income mothers who also do not display any catch-up effects. I also find a substantial heterogeneity inWest and East Germany. Because the reform aimed at parents with strong labor market attachment, the positive effects in the East suggest that the economic incentives essentially perform well, but their impact may be hampered by unfavorable institutional and cultural conditions in the West.
Keywords: J13; J18; J20; K36; 330; fertility; family policy; reform; parental leave; Germany